The Croods = Crood'lar - Demicco, Kirk; Sanders, Chris; Dreamworks Animation SKG. (Dreamworks Animation SKG, 2013)
After their cave is destroyed, a caveman family must trek through an unfamiliar fantastical world with the help of an inventive boy.
3-6.
K-3.
Language : Turkish, English, Czech, polish, Slovak.
Subtitle : Turkish, English, Czech, polish, Slovak.
Keywords: Movie -- animated films